2022
DOI: 10.4103/jfmpc.jfmpc_89_22
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-dermatologic patterns of Paederus dermatitis in a teaching hospital, South India

Abstract: Background: Paederus dermatitis (PD) is common skin condition occurring in South India caused due to contact with Rove beetle. It is often misdiagnosed due to wide difference in its presentation. The aim of this study was to describe the clinical, sociodemographic, and environmental condition of patient’s presenting with PD. Methodology: A descriptive study was done among all patients diagnosed of PD at the Dermatology department of a teaching hospital in Trichy, South … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 19 publications
3
3
0
Order By: Relevance
“…Similar findings were seen in studies done in Malaysia and in India. [10][11][12] Head and neck was the most common site reported in our study followed by trunk, upper extremity, similar to other studies. [13][14][15][16] Periorbital dermatitis was seen in 13.7% patients, similar to a study done by the Srihari et al, while in a study done by the Gnanaraj et al it was only 4.9%.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Similar findings were seen in studies done in Malaysia and in India. [10][11][12] Head and neck was the most common site reported in our study followed by trunk, upper extremity, similar to other studies. [13][14][15][16] Periorbital dermatitis was seen in 13.7% patients, similar to a study done by the Srihari et al, while in a study done by the Gnanaraj et al it was only 4.9%.…”
Section: Discussionsupporting
confidence: 90%
“…In our study kissing lesions were present in 7.5% patients whereas in other studies 1.6% and 40.2% were noted. 10,14 Most common morphology seen in the current study was erythematous plaques (76.2%) followed by vesicles, pustules, crusts similar to other studies. 10 According to Padhi et al study, papules were the most common morphology observed.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations